The Natural Resource Curse and Fiscal Decentralization - Perez-Sebastian, F.; Raveh, Ohad (Oxford University Press, 2016)
© 2015 The Author.Natural resource abundance is a blessing for some countries, but a curse for others. We show that differences across countries in the degree of fiscal decentralization can contribute to this divergent outcome. Using a large panel of countries covering several decades and various fiscal decentralization and natural resource measures, we provide empirical support for the novel hypothesis. We also study a model that combines political and market mechanisms under a unified framework to illustrate how natural resource booms may create negative effects in fiscally decentralized nations.